Exploring Pragmatic Functions of Deixis in Ariana Grande’s Eternal Sunshine Album - Hafiza Saumi Ramadilla; Efani Margareth Br Ginting; Meisuri Meisuri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to analyze the pragmatic functions of deixis in six selected songs from Ariana Grande’s Eternal Sunshine album. Using Levinson’s (1983) theory of deixis, the study identifies and classifies five types of deictic expressions: person, time, place, discourse, and social deixis. The study employs a descriptive qualitative method and uses documentation as its main data collection technique. A total of 306 deixis were found: 228 person deixis, 33 time deixis, 16 place deixis, 19 discourse deixis, and 11 social deixis. The dominant use of person deixis demonstrates the strong self-expression and emotional engagement of the singer. Time and discourse deixis help shape the emotional timeline of the narrative, while place and social deixis reflect interpersonal distance and roles. The findings reveal that deixis functions not only to maintain textual cohesion but also as a pragmatic tool to construct intimacy, express identity, and evoke emotional resonance in the lyrics.